Humor and the framing of the public sphere and public opinion in Portugal (1797-1834) - Ferreira, Joao (2014)
In his Answer to the Question: What is Enlightenment (1784), Kant puts forward his belief that the vocation to think freely, which humankind is endowed with, is bound to make sure that “the public use of reason” will at last act “even on the fundamental principles of government and the state [will] find it agreeable to treat man – who is now more than a machine – in accord with his dignity”. The critical reference to La Mettrie (1747), by opposing the machine to human dignity, will echo, in the dawn of the 20th century, in Bergson’s attempt to explain humor. Besides being exclusive to humans, humor is also a social phenomenon. Freud (1905) assures that pleasure originated by humor is collective, it results from a “social process”: jokes need an audience, a “third party”, in order to work and have fun. Assuming humor as a social and cultural phenomenon, this paper intends to sustain that it played a role in the framing of the public sphere and of public opinion in Portugal during the transition from Absolute Monarchy to Liberalism. The search for the conditions which made possible the critical exercise of sociability is at the root of the creation of the public sphere in the sense developed by Habermas (1962), whose perspective, however, has been questioned by those who point 2 out the alleged idealism of the concept – as opposed, for example, to Bakhtin (1970), whose work stresses diversity and pluralism. This notwithstanding, the concept of public sphere is crucial to the building of public opinion, which is, in turn, indissoluble from the principle of publicity, as demonstrated by Bobbio (1985). This paper discusses the historical evolution of the concept of public opinion from Ancient Greece doxa, through Machiavelli’s “humors” (1532), the origin of the expression in Montaigne (1580) and the contributions of Hobbes (1651), Locke (1690), Swift (1729), Rousseau (1762) or Hume (1777), up to the reflection of Lippman (1922) and Bourdieu’s critique (1984). It maintains that humor, as it appears in Portuguese printed periodicals from 1797 (when Almocreve de Petas was published for the first time) to the end of the civil war (1834) – especially in those edited by José Daniel Rodrigues da Costa but also in O Piolho Viajante, by António Manuel Policarpo da Silva, or in the ones written by José Agostinho de Macedo, as well as in a political “elite minded” periodical such as Correio Braziliense –, contributed to the framing of the public sphere and of public opinion in Portugal.